Marketing strategies and customer relationship management affecting insurance company acceptance towards customer in Bangkok Metropolitan area - Rittiboonchai, Wisit; Phonghanyudh, Surasak; Pupattanapong, Khawta (Interdisciplinary Research Review, 2016)
The purposes of this research were: (1) To study the marketing strategy and customer relationship management that can affect the insurance company acceptance with customer in Bangkok. (2) To study the insurance company acceptance with customer in Bangkok by personal factors using quantitative research methods. The samples of 1,050 have tested the validity with a panel of experts and determine the reliability by Cronbach Alpha of people in Nakhon Pathom province. The measurement criteria have remained relatively high in the range 0.91 to 0.94 The research found that the analysis insurance company acceptance customer in Bangkok that had different characteristics in terms of age, marital status, occupation-based insurance holding statistically significant. The study of marketing strategy and customer relationship management that can affected the insurance acceptances in Bangkok with Path Analysis. The research found that Insurance company acceptance influenced by direct marketing strategies ( = 0.32) and customer relationship management ( = 0.94) and at the same time. Marketing strategy has resulted in significant indirect effects. Insurance company acceptance ( = 0.75) was statistically significant.